Spiritual Reinforcement Bagi Para Lansia Menghadapi Kematian Berdasarkan 1 Tesalonika 4:13-18 - Franseda Sihite (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2023)
The elderly often experience anxiety when facing death. For this reason, spiritual strengthening is needed for the elderly so they don't dissolve in anxiety. This article aims to explain Spiritual Reinforcement for the elderly based on biblical teachings in 1 Thess. 4:13-18 as a provision for the faith of the elderly to go through old age, especially facing death that will come. This scientific work uses the hermeneutic method with a text exposition approach 1 Thess. 4:13-18. The results of the study concluded that 1 Thess. 4:13-18 can be a spiritual strengthening for believers, especially for the elderly congregation that death is a temporary separation from believers who are still alive (1 Thess. 4:13), the death of a believer is sleeping with Jesus (1Thess. 4:14), and death becomes the door to enter eternal life and the meeting of every believer with Christ (1 Thess. 4:15-18).AbstrakPara lansia sering kali mengalami kecemasan ketika menghadapi kematian. Untuk itu diperlukan penguatan rohani terhadap para lansia sehingga tidak larut dalam kecemasan. Artikel ini bertujuan untuk menjelaskan Spiritual Reinforcement (Penguatan Rohani) terhadap para lansia berdasarkan ajaran alkitab dalam 1 Tes. 4:13-18 sebagai bekal iman lansia menjalani masa tua, khususnya menghadapi kematian yang kelak akan tiba. Karya ilmiah ini menggunakan metode hermeneutika dengan pendekatan eksposisi teks 1 Tes. 4:13-18. Hasil penelitian  menunjukkan bahwa teks 1 Tes. 4:13-18 dapat menjadi penguatan spiritual bagi orang-orang percaya, khususnya jemaat lansia yaitu bahwa kematian adalah perpisahan sementara dengan orang percaya yang masih hidup (1 Tes. 4:13), kematian orang percaya adalah tidur bersama Yesus (1Tes. 4:14), dan kematian menjadi pintu memasuki  kehidup kekal dan berkumpulnya setiap orang percaya dengan Kristus (1 Tes. 4:15-18).